LincRNA profile in clear cell renal cell carcinoma using RNA-seq data - Posa, Ioana (2014)
Tese de mestrado, Bioinformática e Biologia Computacional (Biologia Computacional), Universidade de Lisboa, Faculdade de Ciências, 2015